Reproducibility in Cognitive Hearing Research: Theoretical Considerations and Their Practical Application in Multi-Lab Studies - Heinrich, Antje; Knight, Sarah (Frontiers in Psychology, 2020)
In this article, we consider the issue of reproducibility within the field of cognitive hearing science. First, we examine how retest reliability can provide useful information for the generality of results and intervention effectiveness. Second, we provide an overview of retest reliability coefficients within three areas of cognitive hearing science (cognition, speech perception and self-reported measures of communication), and show how the reporting of these coefficients differs between fields. We argue that practices surrounding the provision of retest coefficients are currently most rigorous in clinical assessment, and that basic science research would benefit from adopting similar standards. Finally, based on a distinction between direct replications (which aim to keep materials as close to the original study as possible) and conceptual replications (which test the same purported mechanism using different materials), we discuss new initiatives which address the need for both. Using the example of the auditory Stroop task, we provide practical illustrations of how these theoretical issues can be addressed within the context of a multi-lab replication study. By illustrating how theoretical concepts can be put into practice in empirical research, we hope to encourage others to set up and participate in a wide variety of reproducibility-related studies.